2021
DOI: 10.3390/ijms22031258
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Metabolism: The Role of Cancer Niche in Immune Checkpoint Inhibitor Resistance

Abstract: The use of immune checkpoint inhibitors (ICI) in treating cancer has revolutionized the approach to eradicate cancer cells by reactivating immune responses. However, only a subset of patients benefits from this treatment; the majority remains unresponsive or develops resistance to ICI therapy. Increasing evidence suggests that metabolic machinery in the tumor microenvironment (TME) plays a role in the development of ICI resistance. Within the TME, nutrients and oxygen are scarce, forcing immune cells to underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 202 publications
(172 reference statements)
0
18
0
Order By: Relevance
“…In fact, cancer cells can regulate immune cells by upregulating nutrient uptake and metabolite production, and as a result, constructing an immunosuppressive TME that promotes cancer cell growth and immune evasion. However, some recent studies have suggested that combining the immune checkpoint inhibitors and metabolic regulating agents can decrease cancer cell metabolism more effectively than either approach used in isolation ( Murciano-Goroff et al, 2020 ; Weng et al, 2021 ). Caution is needed to ensure that treatments of this type only target specific tumor sites to prevent side effects such as systemic toxicity.…”
Section: Tumor Microenvironment and Immunotherapymentioning
confidence: 99%
“…In fact, cancer cells can regulate immune cells by upregulating nutrient uptake and metabolite production, and as a result, constructing an immunosuppressive TME that promotes cancer cell growth and immune evasion. However, some recent studies have suggested that combining the immune checkpoint inhibitors and metabolic regulating agents can decrease cancer cell metabolism more effectively than either approach used in isolation ( Murciano-Goroff et al, 2020 ; Weng et al, 2021 ). Caution is needed to ensure that treatments of this type only target specific tumor sites to prevent side effects such as systemic toxicity.…”
Section: Tumor Microenvironment and Immunotherapymentioning
confidence: 99%
“…The discovery of immune suppression checkpoints has revolutionized the systemic approach to cancer treatment, and tumor immunotherapy has been one of the most successful methods in the field of cancer therapy in recent years [271]. Immune checkpoint blockers (ICBs), including CTLA‐4 inhibitors and PD‐1 inhibitors, which block checkpoint proteins from binding with their partner proteins, have been widely used in oncology [272–275].…”
Section: Applications Of Plasma Proteomics/peptidomics In Covid‐19 An...mentioning
confidence: 99%
“…However, patients who received ICIs treatment can develop primary, adaptive, and acquired resistance (Pérez-Ruiz et al, 2020), limiting the efficacy of these treatments (Chiappa et al, 2021;Dal Bo et al, 2020;Kon and Benhar, 2019;Leonetti et al, 2019;Pérez-Ruiz et al, 2020;Sarmento-Ribeiro et al, 2019;Schoenfeld and Hellmann, 2020). Cancer cells have great biosynthetic demands depleting glucose, AA, and FAs from the TME and inducing immune cells to undergo metabolic reprogramming and affecting their fate and functions (Weng et al, 2021). Cancer cells with high aerobic glycolysis induce a hypoxic and acidic TME, inhibiting the normal metabolism of immune cells, which leads to inhibition of mTOR activity, intracellular interferon-gamma (IFN-γ) production, glycolytic capacity in T cells, and diminished T-cell function (Fumarola et al, 2018).…”
Section: The Crosstalk Between Metabolism and Therapy Resistancementioning
confidence: 99%